RESPON PERTUMBUHAN BIBIT TANAMAN AKASIA (Acacia mangium Willd) TERHADAP BEBERAPA KOMPOSISI MEDIA TANAM - Povi Ariansyah; Merismon; Haris Kriswantoro (Jurnal Ilmu Pertanian Kelingi, 2023)
This study aims to determine the growth response of Acacia plant seedlings (Acacia mangium Willd) to several compositions of planting media. This research This research was conducted at the Forestry Plant Seeding Center (BPTH) Selangit District Selangit, Musi Rawas Regency with an altitude of 110 meters above sea level (M.Dpl). This research uses experimental method with complete randomized design (RAL) Non Factorial, consisting of six treatments four replications. Treatments that implemented in this study are as follows: M0 : Soil without compost,M1 : Mixture of soil with compost in a ratio of 1:1, M2: Mixture of soil with compost ratio of 2:1, M3: Soil mixture with 3:1 ratio compost,M4 : Soil mixture with compost ratio 4:1, M5: Soil mixture with 5:1 ratio. The variables observed in this study were: 1. Plant height (cm), 2.Number of leaves (Helai), 3. Diameter of stem (cm), 4. Root length (cm), 5. Wet weight of groundnut Seedling wet weight (g) and seedling dry weight (g). From the results of this study it can be concluded that for Acacia (Acacia mangium Willd) should use the composition of podzolic soil planting media red yellow soil (PMK) and compost in a ratio of 5:1 (M5).